Narrative Reflection in the Family Medicine Clerkship - Cultural Competence in the Third-Year Required Clerkships - Donna Elliott; Pamela Schaff; Theresa Woehrle; Anne Walsh; Janet Trial (Association of American Medical Colleges, 2010)
Abstract This resource cultivates effective cross-cultural communication skills, which requires an understanding of culture that includes both the physician's and the patient's perspectives. Building on a foundation of cultural awareness, knowledge, and skills students have acquired during the preclinical curriculum, this exercise provides an opportunity for students to continue to refine their narrative reflection skills as they interact with patients in the clinical setting. During the family medicine clerkship, students participate in learning activities that provide the opportunity to explore the rich opportunities of thoughtful reflection and narrative practice. Students also participate in a formative narrative reflection exercise during the clerkship orientation. Each subsequent week of the rotation, the students complete an electronic journal entry based on their clinical encounters that is focuses on the patient/physician interaction. At the end of the clerkship, students demonstrate their ability to reflect on patient care through a final project that is shared with faculty and fellow classmates in a faculty-led wrap-up discussion. A diverse patient population is helpful but not necessary to the success of this experience. Integrating cultural competence into the clinical clerkships allows students to apply cultural competence knowledge gained in the first 2 years of medical education, as well develop clinical skills in caring for patients with a variety of backgrounds. This learning experience has allowed faculty the opportunity to regularly address patient-care experiences that everyone acknowledged were fundamental to patient well-being, but had no particular place in the curriculum. A majority of students find positive educational value in their self-reflections and many comment that the family medicine clerkship has provided the one of the only opportunities they've had during their training for this therapeutic activity.